THE DETERMINATION OF ABSOLUTE PARAMETERS AND ABUNDANCE OF COMPONENTS BINARY SYSTEMS: THE SPECIFICITY AND PROBLEMS - Glazunova, L. V. (Одеські астрономічні публікації, 2013)
Spectroscopic binaries remain a laboratory for testing the stellar atmosphere and the stellar evolution theories. It’s considering problems determination of parameters of components and their errous for example two spectroscopic binaries with the main sequence components BW Boo and OU Gem